Open Science: One Term, Five Schools of Thought - Benedikt Fecher; Sascha Friesike (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2013)
Open Science is an umbrella term that encompasses a multitude of assumptions about the future of knowledge creation and dissemination. Based on a literature review, this paper aims at structuring the overall discourse by proposing five Open Science schools of thought: The infrastructure school (which is concerned with the technological architecture), the public school (which is concerned with the accessibility of knowledge creation), the measurement school (which is concerned with alternative impact measurement), the democratic school (which is concerned with access to knowledge) and the pragmatic school (which is concerned with collaborative research).
Keywords: H42; H44; I28; K11; L17; Z13; 330; Open Science; assessment and review; science 2.0; open access; open data; citizen science; science communication; altmetrics